Revealing Insights: Investigating Pharmacovigilance Knowledge, Attitudes, and Practices at a Leading Tertiary Care Hospital in Faisalabad - Shaheen Nazakat, Muhammad Sajid, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The aim of present cross-sectional survey is to investigate healthcare workers' knowledge, attitude, and behaviour regarding pharmacovigilance at tertiary care hospital, Faisalabad. Methods: The present cross-sectional survey was conducted in tertiary care hospital, Faisalabad. The study populations of Eighty (80) male and female health care workers were included in this study. Demographic data and information about workers' knowledge, attitude, and behaviour regarding pharmacovigilance was collected on an interview schedule administered through custom designed structured Performa. The data regarding healthcare workers' knowledge, attitude, and behavior concerning pharmacovigilance at a tertiary care hospital were analyzed using SPSS. Results: The findings of study depicted a positive relationship between knowledge, attitudes, and practices among healthcare workers. Pharmacovigilance is a critical component of drug safety and plays a crucial role in identifying and managing adverse drug reactions and other drug-related problems. Conclusion: Adequate knowledge, skills, and attitudes towards pharmacovigilance among healthcare workers are essential to ensure the safety of medications and promote better patient outcomes. Study can provide valuable insights into the current state of pharmacovigilance in the region and identify areas for improvement. The also enhancing education and training programs for healthcare workers in pharmacovigilance, fostering a reporting culture for adverse drug reactions and adverse events, and establishing robust pharmacovigilance systems and processes are crucial elements for safeguarding medication safety and efficacy, as well as enhancing patient care. Keywords: Healthcare Workers, Pharmacovigilance, Knowledge, Attitude, Behavior, Cross-Sectional Survey, Tertiary Care Hospital, Faisalabad